Education Systems and Foreign Direct Investment : Does External Efficiency Matter? - Miningoua, Elise Wendlassida; Tapsoba, Sampawende Jules (Taylor and Francis, 2021)
This paper examines the effect of the efficiency of the education system on Foreign Direct Investment (FDI). First, it applies a frontier-based measure as a proxy of the ability of countries to optimally convert the average years of schooling into income for individuals. Second, it shows the relationship between the external efficiency of the education system and FDI inflows. The results show that the efficiency level varies across regions and countries and appears to be driven by higher education and secondary vocational education. Similarly to other studies in the literature, there is no significant relationship between the average years of schooling and FDI inflows. However, the external efficiency of the education system is important for FDI inflows. Improving the external efficiency of the education system can play a role in attracting FDI especially in non-resource rich countries, non-landlocked countries and countries in the low and medium human development groups.